Whole-genome scans provide evidence of adaptive evolution in Malawian Plasmodium falciparum isolates. - Ocholla, H; Preston, MD; Mipando, M; Jensen, A; Campino, S; MacInnis, B; Alcock, D; Terlouw, A; Zongo, I; Oudraogo, J; Djimde, A; Assefa, S; et al. (2014)
Selection by host immunity and antimalarial drugs has driven extensive adaptive evolution in Plasmodium falciparum and continues to produce ever-changing landscapes of genetic variation.We performed whole-genome sequencing of 69 P. falciparum isolates from Malawi and used population genetics approaches to investigate genetic diversity and population structure and identify loci under selection.High genetic diversity (π = 2.4 × 10(-4)), moderately high multiplicity of infection (2.7), and low linkage disequilibrium (500-bp) were observed in Chikhwawa District, Malawi, an area of high malaria transmission. Allele frequency-based tests provided evidence of recent population growth in Malawi and detected potential targets of host immunity and candidate vaccine antigens. Comparison of the sequence variation between isolates from Malawi and those from 5 geographically dispersed countries (Kenya, Burkina Faso, Mali, Cambodia, and Thailand) detected population genetic differences between Africa and Asia, within Southeast Asia, and within Africa. Haplotype-based tests of selection to sequence data from all 6 populations identified signals of directional selection at known drug-resistance loci, including pfcrt, pfdhps, pfmdr1, and pfgch1.The sequence variations observed at drug-resistance loci reflect differences in each country's historical use of antimalarial drugs and may be useful in formulating local malaria treatment guidelines.